Analysis of The Optical Properties of Ag Nanoparticles With The Assistance of Bioreductors of Saga Leaf Extract (Abrus pecatorius L.) - Rahma Sofia Putri; Aldi Budi Riyanta; Wilda Amananti (Universitas Negeri Medan, 2023)
Nanotechnology has become an important and interesting field of physics, chemistry, biology and engineering in recent years. The rapidly growing nanotechnology today is nanoparticles. The characteristic characteristic of nanoparticles is that the particle size is very small in the range (1-100 nm). Silver nanoparticles have been synthesized using saga leaf extract (Abrus pecatorius L.) as a reducing agent. The formation of silver nanoparticles was carried out by adding sage leaf extract to the AgNO3 solution and homogenizing using a magnetic stirrer for 60 minutes. UV-Vis spectrophotometer was used to confirm the formation of silver nanoparticles. Test the inhibition of bacteria using the well method. The results showed that the wavelength values were in the range of 375-395nm.